EVALUATION OF NURSING PAIN MANAGEMENT QUALITY INDEX ON POST-OPERATIVE PATIENTS AT THE DEPARTMENT OF GENERAL AND DIGESTIVE SURGERY, HAI DUONG PROVINCIAL GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the quality indicators of postoperative pain management among surgical patients at the Department of Gastrointestinal and General Surgery, Hai Duong Provincial General Hospital in 2024.Subjects and Methods: A cross-sectional descriptive study was conducted on 295 postoperative patients at the Department of Gastrointestinal and General Surgery, Hai Duong Provincial General Hospital from February to October 2024. The study used the Strategic and Clinical Quality Indicators in Postoperative Pain Management Questionnaire (SCQIPP), which consists of 14 items, to assess the quality indicators of postoperative pain management performed by nurses. The SCQIPP responses were dichotomized into two groups, “agree” and “disagree,” based on a five-point Likert scale. Descriptive statistics were used to analyze the quality indicators of postoperative pain management.Results: Patients aged ≥ 60 years accounted for 39.3% of the study population. Nearly 50% of participants reported that nurses did not routinely assess pain at least three times per day. In addition, 58.6% of patients indicated that they were not given the opportunity to participate in choosing pain relief methods, and 53.2% reported that they did not receive assistance from nurses in positioning to relieve pain.Conclusion: Patients showed positive evaluations regarding nursing interventions for pain relief and the ward environment. However, the proportion of patients agreeing with several indicators related to postoperative pain management remained relatively low. Further training is needed to improve nurses’ knowledge and competencies in postoperative pain management.
Keywords: Pain management, gastrointestinal surgery, nursing, Vietnam